Keterampilan Berpikir Kritis dalam Menyelesaikan Masalah PISA Konten Change and Relationship Ditinjau dari Self-Efficacy - Enggar Eko Prasetiyo; Rooselyna Ekawati (MATHEdunesa, 2026)
This study aims to describe students' critical thinking skills in solving PISA-type mathematical problems related to change and relationships, from the perspective of self-efficacy. This research employed a qualitative descriptive approach with two eighth-grade students from SMP Negeri 3 Surabaya in the 2024/2025 academic year, selected based on high and low self-efficacy levels, while considering similar gender, equivalent mathematical ability, and good communication skills. Data collection techniques included a self-efficacy questionnaire, mathematics ability test, problem-solving test, and task-based interviews. Data were analyzed based on indicators of critical thinking: Focus, Reason, Inference, Situation, Clarity, and Overview. The findings indicate that students with low self-efficacy struggle to identify key information, develop logical strategies, and reflect on their approaches. In contrast, students with high self-efficacy demonstrated more systematic understanding, well-structured problem-solving techniques, and reflective, argumentative reviews. These results suggest that self-efficacy plays a significant role in influencing the quality of students' critical thinking. Therefore, teachers need to design learning strategies that enhance students' self-efficacy, such as by providing appropriate challenges, offering positive feedback, and reinforcing successes, so that mathematics instruction becomes more effective in fostering critical thinking skills.